Penerapan PjBL dalam Pemanfaatan Bahan Dapur untuk Membuat Replika Kekhasan Daerah Siswa Kelas VI SD - Sukma, Iva Nila; Barriyah, Insanul Qisti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
Project-based learning on arts and culture content and elementary school students' skills can really develop children's abilities in terms of knowledge, attitudes, skills and creativity. This is in line with the development stage of elementary school students, namely during the concrete operational period. This research aims to describe the implementation of PjBL which uses kitchen materials to create replicas of regional characteristics for class VI students at Widoro State Elementary School. This research uses a qualitative methodology with descriptive techniques. The main data collection method is carried out through interviews and observation, while additional information collection is carried out through documentation studies during learning and field recording. Primary data was collected using observation studies and interviews. Secondary data collection was carried out by carrying out documentation studies during the implementation of learning and taking field notes. Researchers conducted interviews with other class V teachers, and several class VI students. The results of the research show that the implementation of project-based learning by using kitchen materials to create replicas of regional characteristics for class VI students at Widoro State Elementary School was carried out well and received high enthusiasm from students. PjBL learning can improve skills, knowledge, attitudes, creativity and cooperation between students.